Modern Methods Of Instilling A Sense Of Patriotism In Future Teachers (Eurasian Journal of Learning and Academic Teaching, 2022)
This article describes the possibilities of using educational technologies in raising a sense of patriotism among future teachers. The article also mentions the method of using educational technologies.